The UN Security Council and the Maintenance of Peace in a Changing World - Cai, Congyan (Max Planck Trialogues, 2024)
How can the Security Council maintain international peace in times of global polarisation and contestation about principles of international legal and political order? Three experts with diverse geographic, socio-legal, and ideational backgrounds present their views on the Council's functions and deficits, and on tensions and future trajectories.